أثر استخدام كتاب النحو التطبيقي في إتقان قراءة كتاب التراث لطلاب المرحلة الوسطىفي معهد الحكمة الإسلامي بندار لامبونج - Hamdi, Afifah Rahmanida; Toto Edidarmo; Achmad Fudhaili (Penerbit Minhaj Pustaka, 2025)
This study addresses students' difficulties in learning Arabic grammar (nahwu), particularly in reading classical texts (kitab turats). Interview results showed that traditional teaching methods failed to effectively support students' reading skills. The research aims to examine the impact of using Kitab an-Nahwu at-Tathbiqi on students' ability to read kitab turats. It employs a mixed-method approach with a sequential exploratory design. The study involved 79 middle-level students, with 31 in the experimental group and 26 in the control group. Qualitative data were collected through observation and interviews, while quantitative data were obtained via pretest and posttest. Qualitative analysis followed the Miles, Huberman, and Saldana model, while quantitative data were analyzed using a t-test. Results revealed that the experimental group’s average posttest score (76.90) was higher than the control group’s (61.31), with a significance value of 0.000 < 0.05. This confirms a significant impact of using the applied grammar book. The study’s novelty lies in its practical approach to grammar materials, which effectively enhances reading ability of classical texts, despite the limitation of sample size.